2017
DOI: 10.1002/ijgo.12225
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum β‐hCG and lipid profile in early second trimester as predictors of hypertensive disorders of pregnancy

Abstract: Serum β-hCG might be used as a predictor of hypertensive disorders that complicate pregnancy. Dyslipidemia was not found to be a useful marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Some authors reported that major decrease in PAPPA and PlGF levels occurs only in the second trimester, implying that measurements of these parameters in the first trimester may not be reliable enough (13). Contrary, in several studies biochemical markers such as Beta HCG and PlGF were significantly correlated only with early and not late onset GH/PE (5, 28). According to our study results, serum levels of PAPPA in the first as well as HCG and AFP in the second trimester of pregnancy were significantly higher in women who developed early or late onset GH/PE as well as placental abruption during pregnancy.…”
Section: Discussionmentioning
confidence: 60%
“…Some authors reported that major decrease in PAPPA and PlGF levels occurs only in the second trimester, implying that measurements of these parameters in the first trimester may not be reliable enough (13). Contrary, in several studies biochemical markers such as Beta HCG and PlGF were significantly correlated only with early and not late onset GH/PE (5, 28). According to our study results, serum levels of PAPPA in the first as well as HCG and AFP in the second trimester of pregnancy were significantly higher in women who developed early or late onset GH/PE as well as placental abruption during pregnancy.…”
Section: Discussionmentioning
confidence: 60%
“…Serum β-hCG levels can reflect the functional status of the placenta. When placental ischemia and hypoxia happen, the secretion of β-hCG by trophoblast cells increases [13][14][15]. Placental function is directly related to the occurrence of various diseases during pregnancy and adverse pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In present study, we observed the sensitivity, specificity, positive predictive value and negative predictive value for β-hCG levels for >2MOM were 85.2%, 92.5%, 81.98% and 94.8% respectively. Chowdhary H et al [11] , Pawar P et al [9] , Revankar V M [13] , Soundararajan P et al [4] , Kulkarni N et al [7] , Mazhari F 3 had reported similar findings. In present study, the PIH patients cesarean was done in majority of the cases (77.8%) where as in normotensive patients cesarean was done in 52.0 % and the association was found to be statistically significant between hypertensive and normotensive patients (p< 0.05).…”
Section: Discussionmentioning
confidence: 71%